(untitled) (Revista Argentina de Musicología, 2018)
This work focuses on the analytical approach of the phenomenon of the quote. lts first goal is to obtain a classification of the quoting procedures privileged in a corpus of recent Argentinean electroacoustic works. We will also try to analyze the consequences implicit in the quoting of particular compositions. or of a style or gender for the construction of sense in these works. Lastly. we will evaluate the grade of intervention of the composer in the quoting discourse, or the grade of transformation of the original discourse. This entails attending to procedures of deconstruction/reconstruction, tools that some time ago were almost exclusive to traditional schools of instrumental music.